Electromagnetic characteristics of geodesic acoustic mode in the COMPASS tokamak. (13th October 2017) - Seidl, J.; Krbec, J.; Hron, M.; Adamek, J.; Hidalgo, C.; Markovic, T.; Melnikov, A.V.; Stockel, J.; Weinzettl, V.; Aftanas, M.; Bilkova, P.; Bogar, O.; et al.
Abstract: Axisymmetric geodesic acoustic mode (GAM) oscillations of the magnetic field, plasma potential and electron temperature have been identified on the COMPASS tokamak. This work brings an overview of their electromagnetic properties studied by multi-pin reciprocating probes and magnetic diagnostics. The n = 0 fluctuations form a continuous spectrum in limited plasmas but change to a single dominant peak in diverted configuration. At the edge of diverted plasmas the mode exhibits a non-local structure with a constant frequency over a radial extent of at least several centimeters. Nevertheless, the frequency still reacts on temporal changes of plasma temperature caused by an auxiliary NBI heating as well as those induced by periodic sawtooth crashes. Radial wavelength of the mode is found to be about 1–4 cm, with values larger for the plasma potential than for the electron temperature. The mode propagates radially outward and its radial structure induces oscillations of a poloidal E × B velocity, that can locally reach the level of the mean poloidal flow. Bicoherence analysis confirms a non-linear interaction of GAM with a broadband ambient turbulence. The mode exhibits strong axisymmetric magnetic oscillations that are studied both in the poloidal and radial components of the magnetic field. Their poloidal standing-wave structure was confirmed and described for the first time in diverted plasmas. In limited plasmas their amplitude scales with safety factor. Strong suppression of the magnetic GAM component, and possibly of GAM itself, is observed during co-current but not counter-current NBI.